Rapid and sensitive detection of tenuazonic acid in agricultural by-products based on gold nano-flower lateral flow - Cai, Peiyuan; Wang, Rongzhi; Ling, Sumei; Wang, Shihua (Frontiers in Bioengineering and Biotechnology, 2022)
Tenuazonic acid (TA) is a highly toxic mycotoxin mainly generated by the fungi of Alternaria genus and widely contaminates agricultural by-products. Given the threat of TA to food-security, it is very important to develop rapid and sensitive detection methods for TA monitoring. In this study, gold nano-particles (AuNP) with average diameter near 17.25 nm were prepared, and the developed AuNP-based strip has an assay time of 15 min with visual limit of detection (LOD) of 12.5 ng/mL and threshold of 100 ng/mL. To further improve sensitivity, multi-branched gold nano-flowers (AuNF) with average diameter near 50 nm were prepared and characterized by UV-VIS and TEM, and the established AuNF-based strip has visual LOD of 0.78 ng/mL and threshold of 50 ng/mL within 15min. Both assays were applied to determine TA in apple juice and tomato ketchup, and the results were consistent with that of UHPLC-MS/MS. Thus, these assays could be applied for rapid determination of trace TA in real samples.